Primary Thyroid Disorders in Patients with Endogenous Hypercortisolism: An Observational Study - Eda Demir Onal; Muhammed Sacikara; Fatma Saglam; Reyhan Ersoy; Bekir Cakir (International Journal of Endocrinology)
Cushing’s syndrome (CS) may alter the performance of the hypothalamic-hypophyseal-thyroid axis. We searched for a relationship between hypercortisolism and primary thyroid disorders. The medical records of 40 patients with CS were retrospectively examined. Thyroid ultrasonography (USG), basal thyroid function test results (TFT), and antithyroglobulin and antithyroperoxidase antibodies were analyzed. In 80 control subjects, matched by age and gender with CS patients, thyroid USG, TFTs, and autoantibody panel were obtained. Among the CS patients, 17 had nodular goiter, versus 24 controls (42.5% versus 30%, P>0.05). Among the twenty-five patients with an available TFT and autoantibody panel—before and after surgical curative treatment—autoantibody positivity was detected in 2 (8%) patients before and 3 (12%) after surgery (P=0.48). Regarding TFT results, 1 (2.5%) patient had subclinical hyperthyroidism and 1 (2.5%) had subclinical hypothyroidism, whereas 1 (2.5%) control had hyperthyroidism. In total, 21 (52.5%) patients and 32 (40%) controls had ≥1 of the features of thyroid disorder, including goiter, positive thyroid autoantibody, and thyroid function abnormality; the difference was not significant (P>0.05). The prevalence of primary thyroid disorders is not significantly increased in patients with CS.